PAM50 Subtypes in Baseline and Residual Tumors Following Neoadjuvant Trastuzumab-Based Chemotherapy in HER2-Positive Breast Cancer: A Consecutive-Series From a Single Institution - Pernas, Sonia; Petit, Anna; Climent, Fina; Paré, Laia; Perez-Martin, J.; Ventura, Luz; Bergamino, Milana; Galván, Patricia; Falo, Catalina; Morilla, Idoia; Fernandez-Ortega, Adela; Stradella, Agostina; et al. (Frontiers in Oncology, 2019)
Introduction: HER2-enriched subtype has been associated with higher response to neoadjuvant anti-HER2-based therapy across various clinical trials. However, limited data exist in real-world practice and regarding residual disease. Here, we evaluate the association of HER2-enriched with pathological response (pCR) and gene expression changes in pre- and post-treatment paired samples in HER2-positive breast cancer patients treated outside of a clinical trial. Methods: We evaluated clinical-pathological data from a consecutive series of 150 patients with stage II-IIIC HER2-positive breast cancer treated from August 2004 to December 2012 with trastuzumab-based neoadjuvant chemotherapy. Expression of 105 breast cancer-related genes, including the PAM50 genes, was determined in available pre-and post-treatment formalin-fixed paraffin-embedded tumor samples using the nCounter platform. Intrinsic molecular subtypes were determined using the research-based PAM50 predictor. Association of genomic variables with total pCR was performed. Results: The pCR rate was 53.3%, with higher pCR among hormonal receptor (HR)-negative tumors (70 vs. 39%; P < 0.001). A total of 89 baseline and 28 residual tumors were profiled, including pre- and post-treatment paired samples from 26 patients not achieving a pCR. HER2-enriched was the predominant baseline subtype not only in the overall and HR-negative cohorts (64 and 75%, respectively), but also in the HR-positive cohort (55%). HER2-enriched was associated with higher pCR rates compared to non-HER2-enriched subtypes (65 vs. 31%; OR = 4.07, 95% CI 1.65–10.61, P < 0.002) and this association was independent of HR status. In pre- and post-treatment paired samples from patients not achieving a pCR, a lower proportion of HER2-enriched and twice the number of luminal tumors were observed at baseline, and luminal A was the most frequent subtype in residual tumors. Interestingly, most (81.8%) HER2-enriched tumors changed to non-HER2-enriched, whereas most luminal A samples maintained the same subtype in residual tumors. Conclusions: Outside of a clinical trial, PAM50 HER2-enriched subtype predicts pCR beyond HR status following trastuzumab-based chemotherapy in HER2-positive disease. The clinical value of intrinsic molecular subtype in residual disease warrants further investigation.